Dietary nitrate fails to improve 1 and 4 km cycling performance in highly trained cyclists - McQuillan, J. A.; Dulson, D. K.; Laursen, P. B.; Kilding, A. E. (Journal of the International Society of Sports Nutrition, 2017)
We aimed to compare the effects of two different dosing durations of dietary nitrate (NO3-) supplementation on 1 and 4 km cycling time-trial performance in highly trained cyclists. In a double-blind crossover-design, nine highly trained cyclists ingested 140ml of NO3--rich beetroot juice containing ~8.0mmol [NO3-], or placebo, for seven days. Participants completed a range of laboratory-based trials to quantify physiological and perceptual responses and cycling performance: time-trials on day 3 and 6 (4km) and on day 4 and 7 (1km) of the supplementation period. Relative to placebo, effects following 3- and 4-days of NO3- supplementation were unclear for 4 (-0.8; 95% CL, ± 2.8%, p = .54) and likely harmful for 1km (-1.9; ± 2.5% CL, p = .17) time-trial mean power. Effects following 6- and 7-days of NO3- supplementation resulted in unclear effects for 4 (0.1; ± 2.2% CL, p = .93) and 1km (-0.9; ± 2.6%CL, p = .51) time-trial mean power. Relative to placebo, effects for 40, 50, and 60% peak power output were unclear for economy at days 3 and 6 of NO3- supplementation (p > .05). Dietary NO3- supplementation appears to be detrimental to 1km time-trial performance in highly trained cyclists after 4-days. While, extending NO3- dosing to = 6-days reduced the magnitude of harm in both distances, overall performance in short duration cycling time-trials did not improve relative to placebo.